Capsaicin Attenuates Lipopolysaccharide-Induced Inflammation and Barrier Dysfunction in Intestinal Porcine Epithelial Cell Line-J2 - Zhao, Xiaoya; Dong, Bingqi; Friesen, Marissa; Liu, Shangxi; Zhu, Changqing; Yang, Chengbo (Frontiers in Physiology, 2021)
Capsaicin is a spicy, highly pungent, colorless, vanilloid compound found in chili peppers with anti-inflammatory, antioxidant, anti-cancer, and analgesic properties. However, the protective effects of capsaicin on the pig intestine during inflammation are yet to be explored. This study investigated the effects of capsaicin on the gut inflammatory response, intestinal epithelial integrity, and gene expression level of nutrient transporters in a model of lipopolysaccharide (LPS)-induced inflammation in non-differentiated intestinal porcine epithelial cell line-J2 (IPEC-J2). The results showed that the pre-treatment of cells with capsaicin (100 μM) significantly decreased the gene expression and secretion of proinflammatory cytokines induced by LPS through Toll-like receptor 4 (TLR4)/NF-κB signaling pathway. In addition, pre-treatment of cells with capsaicin also increased both gene and protein abundance of tight junction proteins. Furthermore, pre-treatment cells with capsaicin significantly increased trans-epithelial electrical resistance (TEER) and decreased permeability of fluorescein isothiocyanate-dextran (FD4) from the apical side to the basolateral side compared with the control (P < 0.05). Additionally, pre-treatment of cells with capsaicin upregulated the mRNA abundance of nutrients transporters such as Na+/glucose cotransporter 1 (SGLT1). These results suggested that capsaicin could attenuate LPS-induced inflammation response through TLR4/NF-κB pathway and improve barrier integrity and glucose absorption.